AGENCY THEORY DALAM PERSPEKTIF ISLAM - Mariska Dewi Anggraeni (Jurnal Hukum Islam, 2011)
Since agency theory was founded in 1970 by accountancy experts in the United States, the reliability of accountancy role as information media for people outside company was questioned. Agency theory explaining risk problem between prinsipals and agents resulted from cooperation between prinsipals and agents frequently discusses the role of accounting information as relating media between both sides. The insight discrepancy between prinsipals and agents and the information difference of agents make agents often report invalid asymmetric information to earn expected advantages. This moral hazard urges the prinsipals to implement controlling system to watch management behaviors as amanah holders.